ECOLOGY TUTORING AS PART OF TECHNOLOGY EDUCATION IN SECOND LEVEL OF PRIMARY SCHOOL EDUCATION - PYTEL, Krzysztof (Trends in education, 2009)
Condition of the natural environment is getting worse, so education of young people appears an extremely important task for teachers. Process of shaping and teaching values in people can take part in school or out of school. Ecological consciousness can appear as individual or social. In this article one introduces on area of potential of use technology and ecology in technical education. The article presents chosen aspects of ecology teaching researches by answers to question collected from questionnaires on possibilities, functionalities and accessibilities of ecology in teaching of technical subjects.
Keywords: IT; techniques; didactics; ecology.